Foreign body ingestion in Turkish children - Aydoğdu, Sema; Arikan, Ciğdem; Cakir, Murat; Baran, Maşallah; Yüksekkaya, Hasan Ali; Saz, Ulaş Eylem; Arslan, Mehmet Tayyip (The Turkish Journal of Pediatrics, 2009)
Foreign body ingestion (FBI) is a common problem in the pediatric population. Even though morbidity and mortality due to foreign body ingestion are rare in childhood, they may cause serious anxiety in parents. We aimed to analyze the clinical presentation, etiology and management strategy of FBI in children in our country. Records of children admitting with a history of FBI over a three-year period were reviewed retrospectively. Data regarding gender, age, type of the ingested body, management strategy and outcome of the patients were recorded. Of 176 children, 98 (55.6%) were male. Mean age +/- SD of the patients was 3.75 +/- 4.25 years, and most of the patients were below four years of age (71.5%). Most of the children (64.7%) were seen within 48 hours, and most were asymptomatic. Blue beads attached to a safety pin (a cultural good luck charm) (38.6%), coins (27.8%) and turban pins (18.1%) were the most commonly observed foreign bodies. The blue beads/safety pin were found to be ingested primarily by infants, while ingestion of turban pins was mostly seen in adolescent girls who covered their heads. Localization of the foreign bodies was in the distal small intestine, stomach and esophagus in 61.4%, 23.8% and 14.7% of the cases, respectively. Sixty-nine endoscopic interventions were performed in 61 patients (34.6%), and these accounted for 7.3% of all endoscopic interventions during the three-year period. No major complication was observed during the procedure, and none of the patients underwent surgery. The frequently used accessory devices were retrieval net basket (57.9%), snare for pins (17.3%), tripod forceps and rat-tooth forceps. The blue beads/safety pin and turban pin were the commonly ingested foreign bodies in our center due to cultural factors. Education of the parents and of adolescent girls should greatly reduce the incidence of FBI. Endoscopic removal is safe without any major complications.